PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BALAI BESAR METEOROLOGI, KLIMATOLOGI, DAN GEOFISIKA WILAYAH II, TANGERANG SELATAN - Syifa Auliya Suherman; Edy Krisyanto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of Organizational Culture and Work Discipline on Employee Performance at the the Center for Meteorology, Climatology and Geophysics Region II, South Tangerang. The method used is quantitative methods. The population in this study were employees at the Meteorology, Climatology, and Geophysics Center Region II, South Tangerang. With a total of 60 people. This data collection technique is carried out by taking objects from samples called sampling or respondents, the sampling method using the Saturated Sample Technique. the research sample is 60 respondents. The data analysis method used in the study includes instrument testing consisting of validity testing, reliability testing, classical assumption testing consisting of normality testing, multicollinearity testing, autocorrelation testing, heteroscedasticity testing, multiple linear regression testing, correlation coefficients, determination coefficient tests, hypothesis testing consisting of partial t tests and simultaneous f tests. From the results of this study it can be concluded that Organizational Culture has a positive and significant influence on employee performance with a value of > or or (6.435 > 2.002) and is reinforced with a significance value of 0.000 <0.05. Thus, Ho1 is rejected and Ha1 is accepted. Work Discipline has a positive and significant influence on Employee Performance with a value of > or (6.010 > 2.002) and is strengthened with a significance value of 0.000 < 0.05. Thus, Ho2 is rejected and Ha2 is accepted. Organizational Culture and Work Discipline have a positive and significant influence on Employee Performance with a value of > or (25.534 > 3.16) and is strengthened with a significance value of 0.000 < 0.05. Thus, Ho3 is rejected and Ha3 is accepted. Organizational Culture and Work Discipline on Employee Performance have an effect Y = 10.976 + 0.434 X1 + 0.299 X. The result of the R-square value (determination coefficient) is 0.473, it can be concluded that the variables of Organizational Culture (X1) and Work Discipline (X2) together have a contribution to the influence of the Employee Performance variable (Y) of 47.3% while the remaining 52.7% is influenced by other factors or variables that are not studied..